Suicide framing on online media in Indonesia - Safitri, Reza; Rara Ayunita, (Penerbit Universiti Kebangsaan Malaysia, 2022)
News about suicides in online media is increasingly worrying. This is due to the fact that the news stories often show specific display and details of suicide incidents. This study aims to analyse two online media in framing suicide news and the compatibility of the news of the rules from the press Council in 2019 by using a research method adapted from Matthes and Kohring in year 2008. The data used in this research are 85 articles, with the details of 38 articles from Tribunnews.com and 47 articles from suara.com. This research is important in that, if the news is repeated with high news frequency, the mentioned detailed mode is done explicitly, to hyperbolic reporting, it will be able to cause copycat suicide. It is hoped that the results of this research can provide meaningful input for the Indonesian Press Council to provide guidance to journalists in Indonesia regarding writing suicide reports. The methodology utilised for this research is content analysis of media frames guided by Robert M. Entman and then tabulated using the ward’s method by non-hierarchical clustering. The result of the research shows that online media in Indonesia mostly frame suicide as a crime issue and show in detail the ways in which victims commit suicide. This is opposite of the Press Council’s rules in 2019 who regulated suicide as a mental health issue because it is caused not only by a single factor.